E valuation of modified Sugiura’s procedure in the treatment of esophageal varixes: About 12 cases. - Estefan, Alberto; Lago, Fernando; Carriquiry, Guillermo; Beguiristain, Alberto; Bertullo, Hugo; Liard, Washington (Cirugía del Uruguay, 1985)
A modified Sugiura's procedure was used in 12 patients. Modifications consisted in: operation in one instance through iefl thoraco-frenotomy; esophageal transection with Liard's device or mechanic suture device· ligatures and section of stomachic coronary vein; fun'. doplicature; truncal vagotomy and pylorodigitoclasia.